Records of the Charles Darwin Foundation : Origins (Ascendencia) - Charles Darwin Foundation; Acosta Solis, Misael; Alvarez, A.B.; Bowman, Robert I.; Moore, R.T.; Putney, A.D.; Corley Smith, G. T.; Snow, D. W.; Perry, R.; Wittmer, M.; Zambrano-Torres, A.; Government of Ecuador; et al. (1957)
This artificial collection is an assortment of reports, recommendations, survey documents, histories, and recommendations regarding Galapagos Islands conservation and the establishment of the Charles Darwin Foundation. Some of the materials are duplicates of items in the library collection. Included in this collection is the Charles Darwin Research Station Inauguration Book compiled by R. T Moore. It is an archival binder containing 16 pages of the signatures of the attendees of the inauguration on 21 January 1964, and 42 letters of congratulations to the CDF from dignitaries and conservation organizations worldwide.
The collection contains documents pertaining to Galapagos Islands conservation from INEFAN, UNESCO, INGALA, IUCN. It also contains CDF statutes, CDF histories, Informativo Popular, a CDF newsletter about/for Isabela Island, CDF annual reports to the WWF, Baltra U.S. Military correspondence, and other documents.
English, French, German and Spanish